Analisis Peran Pemerintah Daerah Dalam Meningkatkan Kesadaran Masyarakat Terhadap Dampak Pernikahan Usia Dini Di Sumatera Utara - Daniel Try; Mhd. Zidan Aris Fatih; Rely Noviyanti Lumbantobing (Faculty of Social and Political Sciences, Universitas Singaperbangsa Karawang, Indonesia, 2025)
This study critically examines the institutional role of local governments in enhancing public awareness of the multidimensional consequences of early marriage in North Sumatra. Drawing on secondary data from Statistics Indonesia and an extensive review of empirical and normative literature, the research analyses governmental interventions within the frameworks of child-protection policy. The findings reveal that while local governments have initiated the establishment of a preventive ecosystem, implementation remains constrained by cultural resistance, social inequities, limited fiscal capacity, and insufficient interinstitutional coordination. The analysis underscores that the effectiveness of reducing early-marriage prevalence is not solely contingent upon regulatory availability, but rather on governance consistency, cross-sectoral synergy, and the degree to which protective norms are internalized at family and community levels. Consequently, this study positions the prevention of early marriage as a strategic developmental agenda requiring a holistic, evidence-driven, and socially embedded approach to ensure the fulfilment of adolescents’ fundamental rights. Keywords: Government, Marriage, Early Age